Ongoing Impact of COVID in Gall Stone Disease on Patients and Surgeons. Is This Just The Tip of The Iceberg? A Snapshot From An Upper GI Unit - DANIEL, SUDIN; Chong, Yuki; Yeluri, sashi; Hussain, Abdulzahra; Balachandra, Srinivasan; Khetan, Niraj; Samuel, Nehemiah (British Journal Of Surgical Science, 2022)
Introduction: Covid-19 resulted in a delay to provide cholecystectomy services. We looked at the effects of the delay on patient morbidity, operative difficulty, and training at our upper GI unit. Materials And Methods: Data were collected from patients who had cholecystectomy at the resumption of elective operating services at our DGH. We used Medisec, ICE, and Blue Spire software to collect data regarding previous admissions, investigations, and operative details. A proforma was completed after every operation to record the operative findings and difficulty as per Nassar grades. 101 patients who had cholecystectomy when services resumed from September 2020 after a 5-month pause were included in the study. We looked at the initial presentation, number of hospital visits, inpatient admissions, diagnoses, operative difficulty, post-operative complications, hospital stay, 30-day readmissions, and mortality. Results were compared with Chole S study. Results: We found a 50% rise in acute cholecystitis, nearly double the number of pancreatitis and an almost 3 times rise in complications due to choledocholithiasis. Readmissions whilst waiting had increased by nearly 50%. Nassar grade 4 operations were 50% more, with a significant increase (p<0.0001, 95% CI) in the operating time. Complications including bile leak were significantly higher, (p<0.0001, 95% CI). Two-thirds of the operations were done by consultants. Conclusion: This study from an upper GI unit is a testimony to the adverse effects of delay caused by covid in terms of morbidity, hospital resources, and training.